2007
DOI: 10.1177/1470593107073843
|View full text |Cite
|
Sign up to set email alerts
|

Preference reversals resulting from a market value heuristic

Abstract: Two studies demonstrated preference reversals using consumer products. Some subjects made a choice between a pair of food or hygiene products while others assigned minimum selling prices to each product. Product pairs were selected such that one item had a high market price but was undesirable (e.g. eggplant roulettes) while the other item had a low market price but was desirable (e.g. a can of soda). As predicted, most subjects choose the low market price/desirable item, but the high market price/undesirable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…A further prediction of the current research is that the weighting attached to the relative wage will differ across these two choice procedures. This prediction is informed by a series of preference reversals reported in Amir et al (2008) and in Boothe et al (2007). Boothe et al attribute these reversals to the Market Value Heuristic.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A further prediction of the current research is that the weighting attached to the relative wage will differ across these two choice procedures. This prediction is informed by a series of preference reversals reported in Amir et al (2008) and in Boothe et al (2007). Boothe et al attribute these reversals to the Market Value Heuristic.…”
Section: Introductionmentioning
confidence: 89%
“…Boothe et al, 2007;Amir et al, 2008). The prediction that relative wage is likely to be weighted more heavily in choice than in experience stems from findings on rules (e.g.…”
Section: Modelmentioning
confidence: 97%
“…Besides, PR has been replicated in both individual and group responses (Mowen & Gentry, 1980; cf., Berga & Moreno, 2020), has been identified in interpersonal comparisons between single and two or more payoffs (Bazerman et al, 1992), and has been observed more robust than the common consequence effect, or the so-called the Allais paradox, over varying outcome magnitudes (Oliver & Sunstein, 2019). Although much of the work was largely driven by findings in more artificial experimental settings, PR is also unlikely to disappear in more realistic scenarios such as in incentivized experiments (Grether & Plott, 1979), in real-world markets (Bocquého et al, 2013; Boothe et al, 2007; Chen et al, 2020; List, 2002; Lusk, 2019), in real-world lotteries (Ball et al, 2012; Bohm & Lind, 1993; Kachelmeier & Shehata, 1992; Lichtenstein & Slovic, 1973), in different pricing formats (Berg et al, 1985), and among highly trained specialists such as bank employees and finance students (Bohm, 1994b). Moreover, PR has also been transcended from the domain of classic monetary lotteries to the ones including, for example, intertemporal choices between smaller-sooner and larger-later options (Gerber & Rohde, 2010) and medical treatments (Oliver, 2013).…”
mentioning
confidence: 99%
“…Therefore, it appears that one's valuation of an item is readily anchored to some external reference. In another study, Boothe, Schwartz, and Chapman (2007) found that there was preference reversal between a less preferred item that has higher market value (eggplant roulettes) and a more preferred item that has low market value (Coke). In a between-subjects experiment, when asked about which item was preferred between the Coke and eggplant roulettes, participants preferred the Coke.…”
Section: Chapter 1 Introductionmentioning
confidence: 96%